ANALISIS PELATIHAN KERJA PADA UNIT INFORMATION TECHNOLOGYSUPPORT DALAM MENINGKATKAN PRODUKTIVITAS KARYAWAN - Hakim, Avrillia Dewi; Asriati, Nuraini; Rosyid, Rum (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractPT Bank Tabungan Negara (BTN), Pontianak branch especially in units of IT Support had a problem such as the installation of the licensed applications and in fact applications installed to support work is not the applications that have a license but applications are illegal. Then occurrence of some software damage caused by the use of software is inappropriate so the unit IT Support experience or face obstacles in running the program unit. The purpose of this research is to know how job traning in units of Information Technology (IT) Support in increase productivity an employee of PT Bank Tabungan Negara (BTN) branch Pontianak. The method used is methodology qualitative, with a population is four poeple. Data is collected by direct observation technique (sheets of observation), direct communication technique (interview), and study of documentaries. Analysis data using descriptive analysis. The result of this research showed that increase the productivity employees in units of Information Technology (IT) Support after get a full training in accordance with targeted company which is measured by Standard Operating Procedures (SOP). Keywords: Job Training, Units of Information Technology (IT) Support, Productivity Employees